Encountering Prospective Teachers’ and Lecturers’ Lesson Study for Learning Community (LSLC) Experience in Microteaching Class - Yuli Tiarina; Harwati Hashim; Yenni Rozimela; Aryuliva Adnan (English Department FBS UNP, 2021)
Considering the effectiveness of Lesson Study as a continue teacher development, this study was conducted to explore prospective teachers’ and lecturers’ experience in implementing Lesson Study in Microteaching class. Quantitative research approach was employed where a total of 49 prospective teachers and 2 Microteaching lecturers at English Department of Universitas Negeri Padang were involved as the participants. The data were gathered through questionnaires with 1-5 Likert scales consisting of four sessions. The results indicate that prospective teachers and lecturers have positive experience in implementing lesson study for learning community with the mean score 3.75 and 4.08 out of 5. It is supported by the Mann Whitney U test where the value with 1-tailed (.358) was bigger than level of probability α (0.05). They perceived that LSLC promotes to improve the ability of collaboration between members of the learning community and facilitates the process of teaching and learning in Microteaching classes in preparing teaching material and teaching strategies for teaching in microteaching class. Therefore, it is suggested that LSLC must be implemented continuously to improve teachers’ pedagogical competency and collaboration skills.